The Katipunan and the revolution: memoirs of a general with the original Tagalog text - Alvarez, Santiago V., 1872-1930; Paula Carolina S. Malay; Ruby R. Paredes (Loyola Heights, Q.C : Ateneo de Manila University Press, 1996)
English and Filipino text.
Includes index.
Keywords: Philippines -- Hist -- Revolution, 1896-1898; Alvarez, Santiago V. , 1872-1930